The teaching of business ethics: A survey of AACSB member schools - Schoenfeldt, Lyle F. (Journal of business ethics, 1991)
This report presents the findings of a survey of business ethics education undertaken in the Fall of 1988. The respondents were the deans of colleges and universities associated with the AACSB., Ethics, as a curriculum topic, received significant coverage at over 90 percent of the institutions, with 53 percent indicating interest in increasing coverage of the subject. The tabulations of this survey may prove useful to schools seeking to compare or develop their emphases in business ethics.